(untitled) (Mediscope, 2016)
Stress word defined as psychological and physiological dimensions where it derived from physics and mechanics. The banking sector is one of the high stress creating sectors among the women workers. The objectives of this study are to determine the level of stress experienced by the working women and the factors cause stress and also an attempt was made to understand the phenomenon of various coping strategies adopted by working women in baking sector in Bangladesh. The study was a descriptive cross-sectional study among 60 currently working women in different banks in Dhaka city, Bangladesh where purposive random sampling method was used to select sample size. It was estimated by this study that more than 43% of the working women faced high stress of the age group of 20-29 and those had bachelor degree only and also 62% had 1-5 years work experienced were faced high stress. 28% working women regularly felt stress in their profession in banking sector, workload was major factor of stress reported by 65% and 80% women reported that they felt stress due to low salary, job insecurity, transfer and lack of opportunity for growth and advancement; those were mostly responsible creating stress among the working women in banking sector. On the other hand, 55% participants of this study regularly felt anxiety and 33% participants felt throat pain, 47% felt body aches and pain, half felt tiredness, more than half felt anger and frustration, 47% felt back problem and 32% felt high absenteeism and sickness regularly due to stress but very few numbers of the women did yoga, physical exercise and meditation; those were effective to reduce stress. To reduce the stress level among the working women, seminars and workshops should be organized to deal with stress and women should not stay too long or unnecessarily at workplace, and they should avoid multiple tasks at a same time. Moreover, the government should also originate friendly and encouraging policies in favour of working women to encourage them; those will support them to work friendly without stressing. Mediscope Vol. 3, No. 1: January 2016, Pages 1-7